Joseph Stalin & Vladimir Putin: practices of the image construction of a political leader in the discourse of Soviet and Russian media: Иосиф Сталин и Владимир Путин: практики конструирования образа политического лидера в дискурсе советских и российских медиа - Kablukov, Evgenii (Przegląd Wschodnioeuropejski, 2020)
The image of a political leader is considered as a discursive phenomenon, structured by a set of practices. Two practices bring together the images of Stalin and Putin: 1) use of specific nominations of a leader; 2) reproduction of laudatory slogans addressed to a leader. The gatekeeping practices and the content of leaders’ images in considered discourses are fundamentally different. The modern Russian media select the most spectacular breaking news with the participation of Putin and construct the star image, well sold to the Russian consumer. Soviet media refuse any sensationalism, covering only official and routine events with the participation of Stalin. So the contradiction is revealed between the ordinary actions of the leader and the endless praise for Stalin as a deified father.